2008
DOI: 10.1007/s00418-008-0495-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical pattern of the complex innervation of neuroepithelial bodies in mouse lungs

Abstract: As best characterized for rats, it is clear that pulmonary neuroepithelial bodies (NEBs) are contacted by a plethora of nerve fiber populations, suggesting that they represent an extensive group of multifunctional intraepithelial airway receptors. Because of the importance of genetically modified mice for functional studies, and the current lack of data, the main aim of the present study was to achieve a detailed analysis of the origin and neurochemical properties of nerve terminals associated with NEBs in mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 58 publications
5
59
0
Order By: Relevance
“…Furthermore, ATP regulates diverse processes involved in host defense such as anion transport, ciliary function and mucin expression and is also suggested to function in wound repair [126][127][128]. ATP-mediated P2 purinergic receptor activation promotes bronchial epithelial migration and epithelial repair.…”
Section: Pulmonary Epithelium Injurymentioning
confidence: 99%
“…Furthermore, ATP regulates diverse processes involved in host defense such as anion transport, ciliary function and mucin expression and is also suggested to function in wound repair [126][127][128]. ATP-mediated P2 purinergic receptor activation promotes bronchial epithelial migration and epithelial repair.…”
Section: Pulmonary Epithelium Injurymentioning
confidence: 99%
“…In various other cell types (e.g. smooth muscle cells, breast cancer cells, ventricular cardiomyocytes) CaSR activation has been reported to mediate Ca 2+ entry through TRPC-encoded receptor-operated and store-operated channels (Chow et al, 2011;El Hiani et al, 2009;Sun et al, 2010 (Brouns et al, 2009a;Brouns et al, 2012;De Proost et al, 2009), and well-organized intercellular communication could be essential for normal physiology. Apart from its role in interactions between synaptic NEB cells and nerves (Sorokin and Hoyt, 1989), paracrine signaling between ATP-releasing NEB cells and P2Y 2 ATP-receptor-expressing Clara-like cells has been described after depolarization (De Proost et al, 2009) and specific stimulation of NEB cells .…”
Section: Discussionmentioning
confidence: 99%
“…Mouse NEBs express CGRP (Brouns et al, 2009a;Uddman et al, 1985), a neuropeptide encoded by the calcitonin gene via tissuespecific RNA processing (Rosenfeld et al, 1983); calcitonin was also reported to be expressed in mouse NEBs (Luts et al, 1991). As a secretory product of thyroid C-cells, calcitonin is well known as an important mediator in thyroid and parathyroid control of [Ca 2+ ] o homeostasis (Freichel et al, 1996;Garrett et al, 1995), in which the CaSR is the key [Ca 2+ ] o sensor (Chang and Shoback, 2004;Riccardi and Kemp, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations